Estudo comparativo do efeito de três diferentes surdinas na sonoridade de seis violinos: alterações na intensidade e no espectro harmônico - Marcus Vinicius da Silva Evangelista (2019)
The present research investigates the effects produced by three different mutes in the sonority of six dissimilar violins, by means of comparing their sound emission in four study conditions: without mute and with each of the three mutes. The sound intensity (measured in RMS) and changes in the harmonic spectrum produced by the devices are analysed in isolated notes and averages of selected notes; it is also used, for spectral analysis, the LTAS, by means of which an overview of the effect of each mute is obtained on the spectral characteristics of the violins analyzed. From the analysis of these two parameters, in different instruments, the main characteristics of the effects produced by each types of mute in the sonority of the instruments are described, establishing a relation between the different physical characteristics of the mutes and their specific effects on the instrument's original sonority.